Industry 4.0? Framing the Digital Revolution and Its Long-Run Growth Consequences - Jakub Growiec (Gospodarka Narodowa. The Polish Journal of Economics, 2023)
Are we going through a Fourth Industrial Revolution or a technological breakthrough event of an entirely different nature? In this paper, based on the hardware-software framework [Growiec, 2022; Growiec, Jabłońska, Parteka, 2023], I identify the key differences between the technologies of the Industrial Revolution (expanding our capacity to perform physical action) and the Digital Revolution (expanding our capacity to process information). I discuss the implications of these technologies for long-run economic growth, technological progress and factor demand. I find that these implications depend on the possibility of full automation of production processes, the extent of technology spillovers in R&D, and the rate of technological decay. Full automation is disruptive because it makes human labour inessential for production, potentially leading to technological unemployment as well as growth acceleration. Under positive technology spillovers in R&D, technological progress and the accumulation of R&D capital can form a dual growth engine, sustaining exponential growth even under partial automation and without population growth. As an application of the theory, I overview the effects of specific existing and hypothetical digital-era technologies, from the Jacquard loom to artificial superintelligence, for the pace of long-run growth and predicted trends in employment and factor shares.